Complete metagenome sequencing based bacterial diversity and functional insights from basaltic hot spring of Unkeshwar, Maharashtra, India - Mehetre, Gajanan T.; Paranjpe, Aditi S.; Dastager, Syed Gulam; Dharne, Mahesh S. (Genomics Data, 2016)
Unkeshwar hot springs are located at geographical South East Deccan Continental basalt of India. Here, we report the microbial community analysis of this hot spring using whole metagenome shotgun sequencing approach. The analysis revealed a total of 848,096 reads with 212.87Mbps with 50.87% G+C content. Metagenomic sequences were deposited in SRA database with accession number (SUB1242219). Community analysis revealed 99.98% sequences belonging to bacteria and 0.01% to archaea and 0.01% to Viruses. The data obtained revealed 41 phyla including bacteria and Archaea and including 719 different species. In taxonomic analysis, the dominant phyla were found as, Actinobacteria (56%), Verrucomicrobia (24%), Bacteriodes (13%), Deinococcus-Thermus (3%) and firmicutes (2%) and Viruses (2%). Furthermore, functional annotation using pathway information revealed dynamic potential of hot spring community in terms of metabolism, environmental information processing, cellular processes and other important aspects. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of each contig sequence by assigning KEGG Orthology (KO) numbers revealed contig sequences that were assigned to metabolism, organismal system, Environmental Information Processing, cellular processes and human diseases with some unclassified sequences. The Unkeshwar hot springs offer rich phylogenetic diversity and metabolic potential for biotechnological applications.

Characterization of mineral phosphate solubilizing and plant growth promoting bacteria from termite soil of arid region - Chakdar, Hillol; Dastager, Syed G.; Khire, Jayant M.; Rane, Digeshwar; Dharne, Mahesh S. (3 Biotech, 2018)
Five highly efficient phosphate solubilizing bacteria, viz., Pantoea sp. A3, Pantoea sp. A34, Kosakonia sp. A37, Kosakonia sp. B7 and Bacillus sp. AH9 were isolated from termitorial soils of Sanjivani island of southern Maharashtra, India. These isolates were characterized and explored for phosphate solubilization and plant growth promotion. Among these, Bacillus sp. AH9 showed highest phosphate solubilization index (3.5) and solubilization efficiency (250%) on Pikovskaya agar. Interestingly, Pantoea sp. A34 displayed maximum mineral phosphate solubilization (1072.35mg/L) in liquid medium and during this period the pH dropped to 3.13. All five isolates had highest P solubilization at 48h after inoculation. During mineral phosphate solubilization, both gluconic acid and 2-keto gluconic acid were produced by Kosakonia and Bacillus isolates, while only 2-keto gluconic acid was detected in Pantoea isolates. Highest organic acid (39.07 +/- 0.04g/L) production was envisaged in Bacillus sp. AH9, while Pantoea sp. A34 produced the least amount (13.00 +/- 0.01g/L) of organic acid. Seed bacterization with Pantoea sp. A3 and Kosakonia sp. A37 resulted in 37% and 53% increase in root length of tomato seedlings, respectively, while Pantoea sp. A34 and Kosakonia sp. B7 had deleterious effects on root length as well as overall growth of the seedlings. To our knowledge, this is the first report of plant growth promoting potential of microorganisms isolated from termitorial soil of Sanjivani island, which is a drought-prone area. Therefore, such efficient growth promoting P solubilizers can offer an effective solution for sustainable agriculture in arid, dryland farming and drought-prone regions.

Continuous interfacial centrifugal separation and recovery of silver nanoparticles - Deshpande, Jaydeep B.; Navale, Govinda R.; Dharne, Mahesh S.; Kulkarni, Amol A. (Chemical Engineering & Technology, 2020)
Continuous-flow separation and recovery of silver nanoparticles (AgNPs) using an annular centrifugal extractor (ACE) is demonstrated. Separation was achieved at the liquid-liquid interface based on the balance between centrifugal force and the solubility of the capping agent. A mathematical model is presented to understand the mechanism in greater detail. The separation of poly(vinylpyrrolidone) (PVP)-coated AgNPs in an ACE using a strong immiscible solvent was performed. The material accumulated at the interface was separated periodically without discontinuing the operation. The method is also suitable for separation of large particles or 1D/2D nanostructures even employing a single annular centrifugal extractor. Stable AgNPs were selected for a detailed antimicrobial activity study.
Keywords: Annular centrifugal extractor; Antimicrobial activity; Continuous-flow separation; Liquid-liquid interface; silver nanoparticles